METAFORA KONSEPTUAL “POLITIK ADALAH PERANG” DALAM PIDATO KENEGARAAN PRABOWO SUBIANTO - Eva Maria; Merry Lapasau; Kristyan Dwi Aryanto; Rina Maryana; Supendi; Yanti Nuraida (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
Using conceptual metaphors in political speeches can arguably be powerful because speakers need to deliver both the message and the ideological effect to attract the audience’s attention. The study aims to examine the use of metaphors in the first political speech delivered by President Prabowo Subianto during the Plenary Session of the People’s Consultative Assembly of the Republic of Indonesia on October 20, 2024. This qualitative study draws on Critical Discourse Analysis and Conceptual Metaphor Theory. The speech video and its transcript posted on the KOMPAS.TV YouTube channel were chosen as data sources. Four domains of metaphor and four cases of target domain conceptualization were found. These metaphors were conceptualized using several source domains, the most frequent of which is war and physical struggle applied to domestic issues. The findings also suggest that the military characteristics strongly attached to Prabowo Subianto did not produce an aggressive or confrontational rhetorical style. Instead, the source domain of "War" was subtly shifted into metaphors of domestic struggle, economic defense, and bureaucratic cleansing. Results show that the speaker seems to have used the source domains carefully, especially in the case of images containing social and financial elements. This research also demonstrates that the metaphors function as a political communication tool to simplify complex policy ideas into an emergency logic easily understood by the public.